A systematic study on enhancing curing times and thermomechanical properties of SYLGARD™ 186 - John R. Stockdale; Santosh Adhikari; Xavier M. Torres; Adam Pacheco; Shelbie A. Legett; Andrea Labouriau (Results in Materials)
Sylgard 186 is a versatile polydimethylsiloxane (PDMS) elastomer that is cured via a hydrosilylation reaction. Its room temperature curing time is long, leaving much to be desired in terms of application timeframe. Curing the resin at higher temperatures overcomes this problem, but mechanical properties of the cured elastomer tend to deteriorate. Thus, the present work evaluated chemical modifications to the standard Sylgard 186 with the goal to decrease room temperature curing time while maintaining or improving thermomechanical properties. A modified Sylgard 186 formulation that combines the base component of Sylgard 186 with the curing agent of Sylgard 184 in a 30:1 ratio is introduced. The modified Sylgard 186 elastomer displays, after 4 h of curing at 25 °C, Shore A hardness of 29.5 ± 2.8. These results point to a new, readily available, fast curing Sylgard 186 formulation that has the potential to aid in a wide range of applications including potting within microelectronics, mechanobiology, and aerospace components.